O lapidar da palavra na superfície de Uma faca só lâmina - Procópio, Mercia Maria da Silva (2013)
The object of study in this dissertation is the poem "uma faca só lâmina" written by João Cabral de Melo Neto. It aims to get elements that compose the basis of the creation process in this poem, as well as analyze the role of images in the reality representation. The issue focuses on the discussion of a poetry which is built based on the refusal, in the poetic of negativeness based debugging and vacuum, which the view, hear and silence are part of the creation process of the poem. The theoretical and critical reasoning, which supports the work, is based on studies about the poetics of negativity, as, for instance, in the literary space Mallarmé, Maurice Blanchot (2011). The word and object representation supports in critical productions of João Alexandre Barbosa (1975), Benedito Nunes (2007), Marta Peixoto (1983), Solange Rebuzzi (1998). The poet's work presents a poetry laboriously architected. It is a poetry produced according to the calculation, in accuracy, specialy, in this poem, the accuracy of the cabralina poetic blade